Coordination control of hybrid AC/DC building microgrid - Zhu, Dexuan (2017)
Advantages such as environmental friendliness and flexibility have made microgrid an attractive option for in modern power systems. Microgrid is a localized grouping of distributed generators, storages and loads. Microgrid integrates with sustainable energy sources could reduce carbon emission. A microgrid can serve specific purposes, such as to enhance reliability, diversification of energy sources, and cost reduction. Therefore, microgrid has been introduced into building distributed networks as it makes both power generation and consumption more efficient. In order to obtain better power conversion and utilization efficiency, the configuration, control strategy, and energy management of building microgrid need to be further studied. This thesis introduces the overall configuration of building microgrid and the specific subsystem controllers in a building microgrid.